Microbial Terroir in Chilean Valleys: Diversity of Non-conventional Yeast - Jara, Carla; Laurie, V. Felipe; Mas, Albert; Romero, Jaime (Frontiers in Microbiology, 2016)
In this study, the presence of non-conventional yeast associated with vineyards located between latitudes 30ºS and 36ºS was examined, including the valleys of Limarí, Casablanca, Maipo, Colchagua, Maule and Itata. The microbial fingerprinting in each valley was examined based on the specific quantification of yeast of enological interest. Grape berries were sampled to evaluate the presence and load of non-conventional yeast with enological potential, such as Metschnikowia, Hanseniaspora, Torulaspora, Debaryomyces, Meyerozyma and Rhodotorula. These yeasts were present in all vineyards studied but with varying loads depending on the valley sampled. No identical fingerprints were observed; however, similarities and differences could be observed among the microbial profiles of each valley. A co-variation in the loads of Metschnikowia and Hanseniaspora with latitude was observed, showing high loads in the Casablanca and Itata valleys, which was coincident with the higher relative humidity or rainfall of those areas. Non-conventional yeasts were also isolated and identified after sequencing molecular markers. Potentially good aromatic properties were also screened among the isolates, resulting in the selection of mostly Metschnikowia and Hanseniaspora isolates. Finally, our results suggest that microbial terroir might be affected by climatic conditions such as relative humidity and rainfall, especially impacting the load of non-conventional yeast. In this study, the microbial fingerprint for yeast in Chilean vineyards is reported for the first time revealing an opportunity to study the contribution of this assembly of microorganisms to the final product.